The Relationship Between Social Support and Depression on Adolescent Anxiety - Febriani, Diana; Oktaviana, Wita (Indonesian Journal of Global Health Research, 2024)
Adolescents are particularly vulnerable to mental health problems, including depression and anxiety. Depression and anxiety are emotional states that have physilogical characteristics such as tension, discomfort, and negative feelings. Social support is essential for the prevention of depression and anxiety. This study aims to determine the relationship between social support and depression factors on anxiety in adolescents at SMK Muhammadiyah Kartasura. This type of research uses quantitative research with a cross sectional approach. Data collection methods in this study used social support questionnaires and DASS-21 (Depression Anxiety Stress Scale). Validity and reliability tests on the DASS-21 instrument alpha 0.912. The research sample used total sampling of 101 adolescents in class XI aged 15-18 years at SMK Muhammadiyah Kartasura. Data analysis of this study used univariate and bivariate analysis and statistical tests using the spearman test. The results showed no significant relationship between social support factors and depression on anxiety in adolescents with moderate depression and normal anxiety (p value > 0.05). In conclusion, if the social support received by adolescents is not good, then the level of depression and anxiety in adolescents tends to be low.